Do Individual Characteristics Influence the Types of Technostress Reported by Workers? - Marchiori, Danilo Magno; Mainardes, Emerson Wagner; Rodrigues, Ricardo Gouveia (International journal of human-computer interaction, 2019)
Based on the perspective that the diversity of the workforce has implications for attitudes and behaviors at the individual and group levels, this article examines the role of individual differences related to gender, age, formal education, and length of professional experience in the levels of stress caused by the use of information technology (IT) in the daily activities of workers. This phenomenon, termed in the literature as technostress, is studied by identifying and measuring the factors that create technostress (the technostress creator factors: techno-uncertainty, techno-invasion, techno-overload, and techno-complexity). The technostress phenomenon is related to the most varied types of disorders in workers and losses in organizations, such as fatigue, dissatisfaction, anxiety, and reduced productivity. To achieve the goal of this research, we applied structural equation models in a sample of 927 questionnaires completed by 14 different Brazilian public institutions that were distributed among all regions of the country and that were strongly dependent on IT for their main business processes. The results indicate that workers' demographic characteristics relate to one another differently and specifically with the various forms of manifestation of technostress. More precisely, older workers or those with longer professional experience reported greater difficulties with the increase of technological complexity for the execution of tasks (techno-complexity). Women reported being subject to higher levels of techno-complexity and techno-uncertainty, while men indicated feeling greater effects from techno-overload and techno-invasion. We did not detect differences related to the levels of formal education of workers. This study presents the implications of the results for theory and for the everyday life of modern organizations that are increasingly dependent on the use of IT.